2021
DOI: 10.1021/acs.macromol.1c00380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Length on Polymer Stereocomplexation: A Quantitative Study

Abstract: Stereocomplexation critically depends on the chain length and stoichiometry of constituent enantiomeric chains. Quantitative understanding of their independent contribution, however, has long been compromised by inherent molecular weight distribution. In this work, we prepared a library of discrete oligo L-lactide and oligo D-lactide and systematically explored the stereocomplexation behaviors. The relative chain length and mole ratio of the two complementary oligomers can be precisely regulated with predesign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
3
26
0
Order By: Relevance
“…It has been demonstrated that the giant POSS chains with para- configuration could self-assemble into diverse nanostructures, following general self-assembly characteristics as the conventional block copolymers . On the other hand, other factors such as molecular weight distribution, conformational asymmetry, sequence, , and topo-/regio-configuration also have a profound impact on the formation and evolution of ordered structures. The amphiphilic POSS chains prepared in this study consist of an exact number of nanoparticles with precise regio-configuration, serving as an ideal platform to highlight the contribution of the regioregularity in synthetic macromolecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It has been demonstrated that the giant POSS chains with para- configuration could self-assemble into diverse nanostructures, following general self-assembly characteristics as the conventional block copolymers . On the other hand, other factors such as molecular weight distribution, conformational asymmetry, sequence, , and topo-/regio-configuration also have a profound impact on the formation and evolution of ordered structures. The amphiphilic POSS chains prepared in this study consist of an exact number of nanoparticles with precise regio-configuration, serving as an ideal platform to highlight the contribution of the regioregularity in synthetic macromolecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Such properties are not always proportional to chain length, but an abrupt change in a property can be sometimes observed at a certain chain length. [30][31][32][33][34] Crystallization behaviors can often show discontinuous changes as the chain length of an oligomer is increased. [35][36][37][38] In general, shorter oligomers show length-specific lattice cells, conformations (small molecular crystallization), and packing structures, whereas longer ones often crystallize virtually in a similar fashion to one another (macromolecular crystallization).…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38] In general, shorter oligomers show length-specific lattice cells, conformations (small molecular crystallization), and packing structures, whereas longer ones often crystallize virtually in a similar fashion to one another (macromolecular crystallization). Critical chain length, [30][31][32][33][34] which is the division point between these crystallization types (Fig. 1), receives considerable interest because crystal packing and solid-state conformations can alter the physical properties of macromolecules, such as their melting point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A synthetic polymer is virtually a mixture of chains with the same repeating unit but varied chain lengths (known as dispersity , Đ ). It has been recently recognized that the formation and transition of ordered structures are surprisingly susceptible to molecular weight distribution, and even batch-to-batch variation would be sufficient to result in disparate assemblies. , Quantitatively unraveling the role of molecular geometry/architecture demands independent and precise control of molecular parameters to decouple undesired interferences (such as compositional variation). Recent progress in polymer syntheses (e.g., solid-phase synthesis and iterative growth) has allowed the preparation of discrete oligomers/polymers with uniform chain lengths (i.e., Đ = 1). The precision feature offers unparalleled control over chain arrangements, revealing intriguing phase behaviors that have long been compromised by inherent molecular weight distribution and bridging the existing gaps between experiments and theories. ,, In this study, we (i) elaborately designed a library of monomers based on glutamic acid derivatives with similar constitution but varied alkyl side chains and (ii) modularly prepared discrete linear polymers with programmable molecular geometries (Scheme ).…”
Section: Introductionmentioning
confidence: 99%